Zambia : First and Second Reviews of the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waivers of Nonobservance of Performance Criteria, and Augmentation of Access; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director of Zambia. (IMF Staff Country Reports; Country Report ;, 2009)
Zambia's nonperforming loans are expected to increase and banks have become more cautious in their lending. The staff report for the Zambia's first and second reviews of the Three-Year Arrangement under the Poverty Reduction and Growth Facility and request for Waivers of Nonobservance of Performance Criteria, and Augmentation of Access is examined. The slowdown in external demand and uncertainty about the global outlook have negatively affected growth prospects and the balance of payments, and made the program targets for reserve accumulation unattainable.